P197 The improving asthma care together (impact) project. (15th November 2017) - Subramanian, D; Greenwood, S; Dryden, E; Paine, H; Ali, S; Bennet, C; Lagnado, H; Sutton, L
Abstract : The Improving Asthma Care Together (ImpACT) project implements a novel model of care which provides an integrated responsive services for asthma patients in Derby. Aim: The hypothesis of this project was that rapid review by a specialist asthma nurse in the community during an asthma exacerbation, would result in an improvement in patient's asthma control and their ability to self-manage their asthma. Methods: Four specialist asthma nurses were recruited to provide seven day cover for the service. Patients who reported increasing asthma symptoms could access the service by self-referral or referral from a healthcare professional. The intervention involved a face-to-face review or a telephone call from a specialist asthma nurse. Patients were offered a 30 min face to face review at a variety of GP locations in the region. A template for each ImpACT review was constructed and a management plan issued at each consultation. A questionnaire was devised and patients were asked to complete this approximately 6 weeks following the intervention. A 10 point scale was used to ask patient's what their confidence levels were in self-managing their asthma (0=no confidence and 10=highly confident) and how they rated their asthma control (0=poor and 10=excellent). Results: This project commenced in January 2017. Between the start date and June 2017 a total of 884 patients were reviewed as part of the service. 397 face-to- face visits, 470 telephone consultations and 17 home visits. Patient's self-rating of their asthma control significantly improved following the intervention (pre-intervention mean 3.4, standard deviation [SD] 2.2 versus post-intervention mean 8.1 [SD 1.4]; paired t-test <0.001; n=23). Patient's self-reported confidence in managing their own asthma also significantly improved following the intervention (pre-intervention mean 4.1 [SD 2.5] versus post-intervention mean 8.9 [SD 1.1]; paired t-test <0.001; n=24). Total number of hospital admissions and emergency department attendances did not decrease compared to the previous year's data during this period (308 in 2016 versus 352 in 2017). Conclusion: Results to-date show that this integrated and responsive service for asthma exacerbation is well utilised and demonstrates a significant improvement in patient reported asthma control and confidence in self-managing their condition.